1988
DOI: 10.1007/bf01907107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (+)-octanoylcarnitine in intact myocardium

Abstract: Fatty acid metabolites (long-chain esters of CoA and carnitine) which collect in ischemic myocardium can form amphiphiles capable of disrupting subcellular performance. It is important to document the role of these amphiphiles in intact tissue. D-Octanoylcarnitine was chosen because of its previously described effects on inhibiting palmitoylcarnitine transferase (PCT-II) in in vitro and in vivo liver preparations. This inhibition will shift tissue levels of CoA and carnitine intermediates and thus alter amphip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The only one study could be retrieved referred to concentration of 1-oleoylglycerophosphocholine was higher when compared to the normal wild type rat using high mass accuracy electrospray ionization multistage tandem mass spectrometry ( 55 ). In a cohort study of metabolites involved in chronic disease by the effects of vegetarian dietary patterns, vegans showed lower abundance in acylcarnitine, and many subclasses of this metabolite may play a role in insulin dysregulation, inflammation, and so on ( 56 ) together with the effect on myocardium ( 57 ) and arterial stiffness ( 58 )…”
Section: Discussionmentioning
confidence: 99%
“…The only one study could be retrieved referred to concentration of 1-oleoylglycerophosphocholine was higher when compared to the normal wild type rat using high mass accuracy electrospray ionization multistage tandem mass spectrometry ( 55 ). In a cohort study of metabolites involved in chronic disease by the effects of vegetarian dietary patterns, vegans showed lower abundance in acylcarnitine, and many subclasses of this metabolite may play a role in insulin dysregulation, inflammation, and so on ( 56 ) together with the effect on myocardium ( 57 ) and arterial stiffness ( 58 )…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the biochemical pathway of mitochondrial β-oxidation of short-chain saturated fatty acids (Li et al, 2018). It can inhibit palmitoylcarnitine transferase and fatty acid oxidation, thus changing the levels of CoA and carnitine intermediates (DeMaison et al, 1988;May et al, 1980). Morisaki et al (1983) found that decreased fatty acid oxidation was related to increased injuries of brain microvessels.…”
Section: Stepwise Logistic Regression and Roc Analysismentioning
confidence: 99%